Methodical Approach to Measuring The Life Quality in Region - Kozlova, Olga Anatolyevna; Gladkova, Tatyana Viktorovna; Makarova, Mariya Nikitichna; Tukhtarova, Yevgeniya Khasanovna (Economy of Regions, 2015)
The article is devoted to the relevant problem of regional development that is the development of methodological tools to evaluate the life quality in the region. The article discusses the concept of “life quality”, as well as related terms and justifies the author’s position about its content. The existing Russian and foreign approaches to the assessment of life quality were analyzed, and it was argued that a comprehensive approach was the most relevant to conduct this research. The criteria to assess the life quality of the population were summoned. The authors proposed a methodological approach that not only includes the objective indicators of the life quality presented in the statistical reporting of Federal State Statistics Service, but also involves the subjective assessments of the local population, which allows to obtain an adequate assessment of the life quality of the population in the region. The methodological research tools include, firstly, mathematical methods of statistical data processing and, secondly, a sociological survey of the population of Sverdlovsk region about the level of satisfaction with various aspects of life. The authors concluded that stable growth objective indicators of life quality, on the one hand, characterize Sverdlovsk region. On the other hand, simultaneously it is accompanied with low satisfaction with population-specific aspects of life quality, which generally reduces the integral indicator of the life quality of the population, despite the positive dynamics of socio-economic development of the region and an active social policy of the regional authorities. The results of the study were used for the preparation of the regional target program “New life quality of Ural” (decree of the Governor of Sverdlovsk region from 29.01.2014 No. 45-UG “ON the Concept of improving the quality of life of the population of Sverdlovsk region for the period up to 2030 - “a new quality of life of Ural”).